Effects of Physical Activity and COVID-19 on Healthy Student Strengths in the University System: Implications for Post-Pandemic Management - Ramón Gómez Chacón; Jose Manuel Nuñez Sánchez; Pablo Gálvez Ruiz (MDPI AG, 2024)
The COVID-19 pandemic has profoundly affected the physical, mental, and social well-being of millions worldwide. It has also brought about abrupt disruptions to the entire university system, whose students form a crucial segment of society. The pandemic's effects on student education and well-being have been particularly significant. One of the primary consequences has been a drastic reduction in physical activity levels among students, leading to mental and physical health problems. Despite the rapid growth in the literature exploring student experiences during the pandemic, there is a paucity of research on how this decline in physical activity has affected the five strengths of the healthy student: optimism, self-efficacy, resilience, engagement, and hope. Therefore, the aim of this investigation is to examine the relationship between physical activity levels and the five strengths of the healthy student at two different time points (pre-COVID-19 and COVID-19) through the International Physical Activity Questionnaire (IPAQ) and the Healthy Student Questionnaire. The study involved 897 participants, with 290 participating in the pre-COVID-19 phase and 607 participating in the COVID-19 phase. The results revealed significant differences in the five strengths between the two periods. Students who engaged in physical activity exhibited significantly higher optimism scores in the pre-COVID-19 phase. During the COVID-19 phase, physically active students demonstrated significantly higher scores in optimism, resilience, and self-efficacy. These findings provide clear guidance for university administrators seeking to enhance student well-being in a post-pandemic world and in the face of future disruptions. Universities should consider implementing physical exercise programs for their students to promote psychosocial well-being and provide training and resources to equip faculty members with new skills to better understand and support students' perceptions.